Crosstalk between the Rho and Rab family of small GTPases in neurodegenerative disorders - Nik Akhtar, Shayan; Bunner, Wyatt P.; Brennan, Elizabeth; Lu, Qun; Szatmari, Erzsebet M. (Frontiers in Cellular Neuroscience, 2023)
Neurodegeneration is associated with defects in cytoskeletal dynamics and dysfunctions of the vesicular trafficking and sorting systems. In the last few decades, studies have demonstrated that the key regulators of cytoskeletal dynamics are proteins from the Rho family GTPases, meanwhile the central hub for vesicle sorting and transport between target membranes is the Rab family of GTPases. In this regard, the role of Rho and Rab GTPases in the induction and maintenance of distinct functional and morphological neuronal domains (such as dendrites and axons) has been extensively studied. Several members belonging to these two families of proteins have been associated with many neurodegenerative disorders ranging from dementia to motor neuron degeneration. In this analysis, we attempt to present a brief review of the potential crosstalk between the Rab and Rho family members in neurodegenerative pathologies such as Alzheimer’s disease (AD), Parkinson’s disease (PD), Huntington disease, and amyotrophic lateral sclerosis (ALS).